Contaminated land : investigation, assessment and remediation. - Strange, Jo (Thomas Telford, 2008)
This guide supplements and enhances existing authoritative and competent guidance documents prepared by key government and research organisations, such as the Environment Agency, the Construction Industry Research and Information Association and the Building Research Establishment.
Keywords: Soil pollution -- Great Britain.; Waste disposal sites -- Great Britain.; Pollution -- Risk assessment -- Great Britain.; Soil remediation -- Great Britain.; Brownfields -- Great Britain.; Reclamation of land -- Great Britain.; Brownfields -- Risk assessment -- Great Britain.; elektronické knihy; electronic books